TRENDS OF COMMUNICABLE AND NON-COMMUNICABLE MORBIDITIES IN UTTARAKHAND STATE: A SYSTEMIC REVIEW - Kumar, R; Sharma, S K (Indian Journal of Community Health, 2013)
Objective: To identify the trend of communicable and non-communicable morbidities in Uttarkhand state. Methods: This systemic review was conducted using the vide range of literature i.e. published reports of Ministry of Health & Family Welfare, Government of India and Uttarakhand State. The published original research papers from original journals, E-journals and electronic data base such as Medline, Pubmed, Indmed etc. Findings: Uttarakhand is geographically and socio-culturally diverse state because of location and scattered population in hilly and plain region. State has high prevalence of some of the communicable diseases such as tuberculosis (170 cases/Lakh population), malaria (14% in fever cases) and vulnerability of HIV/AIDS. Furthermore, negative lifestyle practices i.e. smoking (20%), tobacco chewing (12%), other form of tobacco use (27%), binge alcohol drinking (52%), low level of physical activity (67%), over weight (14%) and central obesity (18%), consumption of fruits and vegetables less than recommended (89%) are significantly contributing to the ever increasing risk of encountering the non-communicable diseases. Presently over 8% people in Uttarakahnd are hypertensive and 5.7% are diabetic. Conclusion: This hilly, geographically diverse state is having higher prevalence of some of the communicable morbidities such as TB (170/Lakh population) and malaria (14% of all fever cases) and vulnerability for HIV/AIDS. Because of negative life style practices there are increasing trend in prevalence of non-communicable morbidities; presently over 8% people in Uttarakahnd are hypertensive and 5.7% are diabetic. Therefore, a sound healthcare infrastructure is required to meet healthcare needs of the people in state.